Detailed insight into processes of reversible solid oxide cells and stacks using DRT analysis. (15th December 2020) - Subotić, Vanja; Königshofer, Benjamin; Juričić, Đani; Kusnezoff, Mihails; Schröttner, Hartmuth; Hochenauer, Christoph; Boškoski, Pavle
Abstract: This study demonstrates applicability of the distribution of relaxation times (DRT) methodology to reveal more precise analysis of processes that occur in solid-oxide fuel (SOFC) and electrolysis (SOEC) cells of industrial-size as well as 10-layer stacks. Initially, we show that before starting to interpret the data observed, it is necessary to verify the quality of the impedance data measured in order to be used for further analysis. For the purpose of experimental study, operating parameters were varied and their impact on the system performance was determined. When operating cells and stacks very similar specific frequencies were identified, whereby for the stack one additional peak was observed. In the fuel cell mode the main frequency ranges to link with the processes that occur were identified to be 0.01–5 Hz and 50–100 Hz. In the electrolysis mode, the DRT amplitudes observed are lower, but specific frequencies higher, even by a factor of 10. In addition, specific behaviour of DRT-peaks could be correlated to the morphological changes of the Ni-based fuel electrodes that occurred during the stability tests performed. Summarizing this, the results presented in this study show how to: (i) distinguish different processes, (ii) link the knowledge gained from the analysis of single-cell level and subsequently, (iii) transfer it to real stack system. Thus, this study also represents a guideline for a detailed electrochemical performance characterization of high temperature fuel cell and electrolysis systems using the sophisticated DRT tool. Highlights: Approving applicability of DRT approach for real systems. Detailed DRT analysis of both rSOC single cells and stacks. Linking DRT-data observed on different levels. Insight into electrode processes and mechanisms in rSOCs.